A novel mixed resilience engineering and macroergonomics framework for performance evaluation of an insurance company. (13th December 2022) - Sarani, Mehrdad; Hamid, Mojtaba; Bastan, Mahdi; Samieinasab, Mina
Insurance industry has always attracted the attention of researchers because the improved performance of this industry can have a tremendous impact on other manufacturing and service sectors. Therefore, the evaluation and efficiency of active departments in this service area are of great significance. This study evaluated the performance of an insurance company based on Resilience Engineering (RE) and Macroergonomics (ME) and indicators using quantitative and qualitative approaches. For this purpose, after designing a questionnaire and having it completed by 65 experts, the company's performance was analysed using Data Envelopment Analysis (DEA), statistical methods and sensitivity analysis methods. Results showed that considering resilience engineering and macroergonomics can improve the company's performance. Also, it was found that preparedness and information flow indicators were the most important and least important factors influencing the company's performance, respectively. The proposed framework can be used as an effective tool by managers to boost efficiency.